Utredande genetisk genealogi – ett genombrott? – En analys av metodinförandets straffprocessuella betydelse - Pigg,Ellen (2025)
On July 1, 2025, genetic genealogy was introduced as a tool for police investigations in Sweden. The method is also called investigative genetic genealogy and has been praised as a “forensic revolution” and described in terms such as “breakthrough”. However, the fact that no solved crimes have been made public and no convictions have been issued since its commencement raises questions regarding its actual significance in the criminal process. The purpose of this thesis is therefore to examine that significance, on the basis of to what extent Swedish criminal cases can progress from investigation to conviction through investigative genetic genealogy. The use of investigative genetic genealogy is subject to restrictive regulation in Swedish law. For example, the method can only be used following a decision by a public prosecutor in criminal investigations concerning murder, aggravated rape and aggravated rape of a child. In addition, there must be specific grounds to assume that the examined DNA trace was deposited by the perpetrator. Using the method must also be of exceptional importance to the investigation, while its purpose cannot be achieved through less intrusive investigative measures. A number of practical considerations must also be considered. For instance, a DNA trace from the perpetrator must have been deposited at the crime scene. The trace must also have been secured and preserved in the investigation, and be of sufficient quality and quantity to allow a DNA profile to be extracted. Likewise, the produced DNA profile must be of sufficient quality and quantity to be able to be compared in the comparative search. The scope for using this investigative method is therefore severely limited in Sweden, and consequently only a relatively small number of crimes may be investigated using it. In cases where the method is used successfully, however, the prospect of achieving a conviction appear promising. Based on a qualitative analysis of three leading court cases concerning DNA evidence, Swedish courts tend to accord such evidence (including evidence obtained through investigative genetic genealogy) high probative value. This applies particularly to DNA results that demonstrate a clear connection between the trace and the defendant, while also considered reasonable in light of other evidence. Finally, this thesis concludes that the introduction of investigative genetic genealogy in Sweden has had limited significance in the criminal process this far. That should not, however, be understood as an indication of a lack of effectiveness, but rather as a consequence of the framework surrounding the permitted use of the method.
Keywords: Straffrätt; Genetisk genealogi; Utredande genetisk genealogi; DNA-baserad släktforskning; DNA-bevisning; Bevisvärdering; Lagen (2018:1693) om polisens behandling av personuppgifter inom brottsdatalagens område